A new species of Polyarthra Ehrenberg, 1834 belonging to the vulgaris-group (Rotifera: Monogononta: Synchaetidae) from Argentina, with a key to the identification of species in the Neotropical Region - Jose, Susana Beatriz (2011)
A new species of planktonic genus Polyarthra Ehrenberg, 1834 was found in water bodies of north-eastern Argentina along the Paraná River and Uruguay River systems. This species, which belongs to the group that has a pair of ventral additional paddles, shares several features with other species of the genus particularly with P. dolychoptera Idelson, 1925, P. luminosa Kutikova, 1962, and P. indica Segers and Babu, 1999. Polyarthra platensis sp. nov. can be distinguished from other species of the genus by at least two autapomorphic traits, 1) the structure of dorsal integument and 2) the unusual heterogeneity in the composition of paddle bundles. Moreover, this species exhibits a specific combination of diagnostic features including the structure of the trophi having bare manubria, unci with a single tooth and absence of teeth before and after the strong major tooth on the rami. The discovery of this new species indicates that a revision of the genus in the Neotropical Region is pressingly needed. This study provides an updated species identification key for this genus in the Neotropical Region.